Isolation and biochemical characterization of underwater adhesives from diatoms - Poulsen, Nicole; Kroeger, Nils; Harrington, Matthew J.; Brunner, Eike; Paasch, Silvia; Buhmann, Matthias T. (Biofouling, 2014)
Many aquatic organisms are able to colonize surfaces through the secretion of underwater adhesives. Diatoms are unicellular algae that have the capability to colonize any natural and man-made submerged surfaces. There is great technological interest in both mimicking and preventing diatom adhesion, yet the biomolecules responsible have so far remained unidentified. A new method for the isolation of diatom adhesive material is described and its amino acid and carbohydrate composition determined. The adhesive materials from two model diatoms show differences in their amino acid and carbohydrate compositions, but also share characteristic features including a high content of uronic acids, the predominance of hydrophilic amino acid residues, and the presence of 3,4-dihydroxyproline, an extremely rare amino acid. Proteins containing dihydroxyphenylalanine, which mediate underwater adhesion of mussels, are absent. The data on the composition of diatom adhesives are consistent with an adhesion mechanism based on complex coacervation of polyelectrolyte-like biomolecules. © 2014 © 2014 Taylor & Francis.
CRIS-Team Scopus Importer:2023-03-20
Keywords: 3; 4-dihydroxyproline; adhesive material; Amphora coffeaeformis; Craspedostauros australis; diatom; uronic acids